Penerapan Strategi Alpha Zone dalam Pembelajaran Bahasa Arab di Kelas 7 MTs Swasta Tarbiyah Islamiyah Pasia - Annafi, Naufal; Sa’adiyah, Hurriyatus; Putra, Feri Ananda (TSAQOFAH, 2024)
Using alpha brain waves, the alpha zone technique prepares pupils to absorb information more effectively by putting them in a state of readiness to learn. Therefore, in order to accomplish learning goals, pupils need to be in an alpha state. When someone is in alpha state, they will exhibit behaviors like smiling, laughing, and having a positive attitude. A qualitative approach is used in this investigation. This study's data came straight from MTs S TI Pasia's seventh grade Arabic instructor. In addition, documentation, interviews, and observation were the means of data gathering. The results of this research show that by implementing the alpha zone strategy when teaching Arabic, students will feel comfortable when learning. If students feel comfortable when studying, then the student's expression when studying is a cheerful face, smiling, even laughing. If the student's condition is like that, then the student is already in the alpha zone. Students who are in the alpha zone will make students ready to learn and this strategy can make students who initially don't like learning Arabic become like learning Arabic.